2012
DOI: 10.1002/dac.1396
|View full text |Cite
|
Sign up to set email alerts
|

A survey and comparison of multichannel protocols for performance anomaly mitigation in IEEE 802.11wireless networks

Abstract: SUMMARYProviding multichannel functionality can improve the performance of wireless networks. Although off‐the‐shelf IEEE 802.11 physical layer and medium access control specifications support multiple channels and multiple data rates, one of the major challenges is how to efficiently utilize available channels and data rates to improve network performance. In multirate networks, low‐rate links severely degrade the capacity of high‐rate links, which is known as performance anomaly. To overcome the performance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Using a specified value of D, one can estimate a corresponding value of n , yielding the approximate propagation time between the BS and the UE, which is useful. Thus, it can be suggested that (21) and (22) can be employed to combat the random action of the scatterers between the BS and the UE to improve multipath propagation.…”
Section: Bounds On Time-of-arrival Probability Density Functionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Using a specified value of D, one can estimate a corresponding value of n , yielding the approximate propagation time between the BS and the UE, which is useful. Thus, it can be suggested that (21) and (22) can be employed to combat the random action of the scatterers between the BS and the UE to improve multipath propagation.…”
Section: Bounds On Time-of-arrival Probability Density Functionsmentioning
confidence: 99%
“…Even though research work has been performed to improve transmission performance in various systems [19][20][21], propagation delay is still a major difficulty because of many random scatterers. The main goal is to transmit signals from the UE to the BS close to the line-of-sight (LoS) direction, but this is not always possible because of unknown and unexpected obstacles blocking transmission paths.…”
Section: Introductionmentioning
confidence: 99%
“…and avoiding duplicated frame transmission. The core idea behind this strategy is to exploit both time diversity and frequency diversity to send frames over high quality channels [30], increasing the capacity and the range of communications in mesh networks, reducing the collisions occurrence. It consists in temporarily delaying outgoing frames (usually control frames) so that they can be inserted in the next outgoing data frame, reducing the overhead over the access and utilization of the medium.…”
Section: Opportunistic Forwardingmentioning
confidence: 99%
“…Smart antennas and directional antennas. The core idea behind this strategy is to exploit both time diversity and frequency diversity to send frames over high quality channels [30], increasing the capacity and the range of communications in mesh networks, reducing the collisions occurrence. Briefly, directional antenna takes advantage of the PHY geometry of the antenna to provide a transmission power gain because energy is focused in a narrow direction rather than spread (e.g., in omnidirectional antennas).…”
Section: Network Coding Increases Transportationmentioning
confidence: 99%
“…The performance of the IEEE 802.11 DCF scheme has been extensively studied in the literature using different methods and simplifying assumptions. Because of the lack of a comprehensive model, this performance analysis has been going on up to now . Bianchi's 2D Markov chain model is the first and mostly used one (because of its simplicity) describing the BEB mechanism of DCF.…”
Section: Related Pieces Of Workmentioning
confidence: 99%